Deconstructing the Reality of Community-Based Management of Marine Resources in a Small Island Context in Indonesia - Gorris, Philipp (Frontiers in Marine Science, 2016)
This study offers a detailed analysis of community-based management (CBM) in a small island in Indonesia. In the study site, area-specific stewardship for a marine territory was informally institutionalized and, in addition to state rules, locally devised rules based on informal agreements have emerged. Using multiple methods for the analysis of the perceptions of the local community, this research examines the actual impact of the different rules on the fishing patterns in that sea territory, and illuminates the rationales of the local population to engage (or not) in the community-based approach to manage the marine resources. The study shows that the CBM initiative has to be seen as part of a convoluted regulatory system that impacts the fishing behavior in the sea territory. A lack of official authority to formally develop and especially to locally enforce rules represents a key challenges for the CBM initiative. This is further complicated by severe coordination problems between the local community and higher level state actors. The study further shows that the motivation of the community members to engage in the enforcement of the informal rules is strongly based on short-term economic considerations. For rules that are perceived to have a strong impact on the individual fishing yields, the fear of potential short-term economic losses constitutes a particular success factor of the local initiative since it motivates the members of the community to enforce local rules, especially when outside fishers break the rules. Yet, if rule-breaking is not perceived to decrease individual fishing yield, or if benefits of the generated yields are shared with the community as a compensation mechanism, the motivation of the community members to engage in rule enforcement ceases.